ẢNH HƯỞNG CỦA THAN CHÌ VÀ MOLIPDEN DISUNFUA TỚI HÌNH THÁI VÀ TÍNH CHỊU MÀI MÒN CỦA VẬT LIỆU COMPOSITE NỀN POLYETYLEN TRỌNG LƯỢNG PHÂN TỬ SIÊU CAO - Nguyễn, Đức Anh; S. V., Panin (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE IMPACT OF GRAPHITE AND MOLYBDENUM DISULFIDE ON STRUCTURE AND PROPERTIES OF COMPOSITE MATERIALS BASED ON ULTRA HIGH MOLECULAR WEIGHT-POLYETHYLENE The effect of various fillers (graphite, MoS2) on the mechanical and tribological properties of ultra high molecular weight polyethylene (UHMW-PE) is studied. The modification of UHMW-PE by graphite or MoS2 leads to a substantially enhance in its tribological properties but not change substantially their mechanical properties. The results of analysis SEM shows that modification UHMW-PE by these fillers leads to the formation of supramolecular spherulitic structure. The friction resistance of UHMW-PE increases about two times with 5% graphite (particle size 2 - 3 μm).